Inovasi Pelayanan Kartu Sehat Berbasis Nik Untuk Masyarakat Kurang Mampu Di Kota Bekasi - Mutia Ariska Harani; Galih Wahyu Pradana (Universitas Negeri Surabaya, 2022)
Today, health is one of the most important aspects of life. The government has an obligation to be able to help meet the needs of the community in health services. One of Bekasi City's ideas is to create a Healthy Bekasi, by implementing a health service innovation in the form of a NIK-based Health Card. This study aims to determine the innovations carried out by NIK-based health card services in Bekasi City. The approach in this research is to use a qualitative descriptive approach using three dimensions, namely product, environment, and organization. The results of this study are viewed from three dimensions, namely product, environment, and organization, as well as the obstacles that occur. The production innovation carried out by the Bekasi KS-NIK is considered successful due to the role of technology in improving the management of the KS-NIK participant database and the dashboard of the KS-NIK management system. In terms of the environment, the enthusiasm of residents of Bekasi City and outside Bekasi City for the Healthy Bekasi Card is very high in terms of devices, channels, and user behavior. The application of the KS-NIK is considered to still experience shortcomings because there are still complaints from the Hospital (as a provider) about the low service rates in hospitals and for primary health facilities. KS-NIK innovation is also inseparable from obstacles, as for the obstacles that occur, namely the existence of social and political issues that stop the KS-NIK Jamkesda Program. Keywords: innovation, health card, Bekasi City, service.